2022
DOI: 10.3389/fonc.2022.983537
|View full text |Cite
|
Sign up to set email alerts
|

INPP4B inhibits glioma cell proliferation and immune escape via inhibition of the PI3K/AKT signaling pathway

Abstract: INPP4B (Inositol polyphosphate 4-phosphatase type II) has been regarded as a suppressor of several human tumors, but its biological function, expression, and clinical significance in glioma tissues and cell lines are unclear. Notably, whether INPP4B participates in immune escape of glioma deserves urgent attention. Here, we confirmed that INPP4B expression is often downregulated in low- and high-grade human glioma tissues, in tissues from an orthotopic mouse model of brain glioma and in glioma cells. We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Additionally, potential differences in the PI3K-AKT-MTOR and epithelial-mesenchymal transition for the high-and low-risk subtypes were strati ed by functional enrichment analysis. PI3K-AKT signaling pathway has been proven to mediate glioma migration, invasion, proliferation and EMT activities [43][44][45][46] .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, potential differences in the PI3K-AKT-MTOR and epithelial-mesenchymal transition for the high-and low-risk subtypes were strati ed by functional enrichment analysis. PI3K-AKT signaling pathway has been proven to mediate glioma migration, invasion, proliferation and EMT activities [43][44][45][46] .…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of the cell cycle is a crucial mechanism for the infinite proliferation and metastasis of malignant glioma cells [47]. PI3K-AKT signaling pathway is an essential intracellular signal pathway that is directly involved in regulating glioma cell proliferation, EMT, migration, invasion, and immune escape [48][49][50][51]. As a complex extracellular macromolecular network, ECM controls multiple cellular activities, such as adhesion, migration, and proliferation [52].…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of INPP4B inhibited glioma cell proliferation, migration, apoptosis resistance, PD‐L1 expression, and T cell suppression. Mechanistic findings suggest that INPP4B inhibits immune escape from glioma by downregulating PI3K/AKT signaling and thereby suppressing PD‐L1 expression 47 . The PD‐1 expression on tumor‐infiltrating T cells from glioma cell suspensions was examined and the circulating T cells was simultaneously isolated.…”
Section: Characteristics Of the Components Of The Glioma Immune Micro...mentioning
confidence: 99%
“…54 INPP4B expression is significantly reduced in gliomas, and overexpression of INPP4B inhibits glioma cell proliferation, migration, apoptosis resistance, PD-L1 expression, and T-cell suppression. Mechanistic findings showed that INPP4B inhibited PD-L1 expression and thus glioma immune escape through downregulation of PI3K/AKT signaling 47.…”
mentioning
confidence: 99%